'When there's no underbrush the tree looks taller': A discourse analysis of men's online groin shaving talk. (December 2015) - Hall, Matthew
It seems many men continue to be obsessed with their penis and especially its size and look. Two-thirds of men in a recent UK study reported some dissatisfaction with their genitals. Arguably much of this anxiety is perpetuated by the media and marketers, but it may also follow more general trends in male body image consciousness. Marketers have been quick to offer both surgical and non-surgical remedies to help change the size, shape and image of the penis, especially online. Stepping aside from more traditional scholarly foci on culture, media, social and personal relationship issues, I focus instead on how men account for pubic hair shaving to enhance image. I use discourse analysis to examine online electronic dialogue in response to an advert promoting male groin grooming showing the complex ways in which men discursively negotiate their interest in this non-typical gender practice. The analysis shows charges of vanity are swept under the carpet in favour of heterosexual pleasure, cleanliness, self-respect and individuality. The implications for understanding traditional and contemporary masculinities are also discussed.